2014
DOI: 10.1063/1.4882995
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport properties of inner and outer shells in near ohmic-contacted double-walled carbon nanotube transistors

Abstract: We investigate electronic transport properties of field-effect transistors based on double-walled carbon nanotubes, of which inner shells are metallic and outer shells are semiconducting. When both shells are turned on, electron-phonon scattering is found to be the dominant phenomenon. On the other hand, when outer semiconducting shells are turned off, a zero-bias anomaly emerges in the dependence of differential conductance on the bias voltage, which is characterized according to the Tomonaga-Luttinger liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Even more, based on DOS calculations for labels J and K, only metallic behavior is noticed, for four CNTs involved [(13,13), (12,12), (14,0), and (12,0)] and the two implicated DWCNTs. This issue agrees with Zhang et al who performed electrical measurements on M@S type of DWCNTs and reported that different electron transport behaviors emerge when the outer semiconducting shell is on/off, which reveals that both the outer and the inner shells of the DWCNTs contribute considerably to the electron transport with ohmic contact. In Figure S5 it was included a collage with DOS plots for case C2, where it can be evidenced overlapping orbitals for DWCNT only for labels J/K.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Even more, based on DOS calculations for labels J and K, only metallic behavior is noticed, for four CNTs involved [(13,13), (12,12), (14,0), and (12,0)] and the two implicated DWCNTs. This issue agrees with Zhang et al who performed electrical measurements on M@S type of DWCNTs and reported that different electron transport behaviors emerge when the outer semiconducting shell is on/off, which reveals that both the outer and the inner shells of the DWCNTs contribute considerably to the electron transport with ohmic contact. In Figure S5 it was included a collage with DOS plots for case C2, where it can be evidenced overlapping orbitals for DWCNT only for labels J/K.…”
Section: Resultssupporting
confidence: 91%
“…In other combinations, a significant difference in the transmission was evaluated for some M@S and S@S systems, compared to that found for the individual tubes. Finally, Zhang et al have investigated electronic transport properties of field‐effect transistor based on DWCNT, particularly those that inner shells are metallic and outer shells are semiconducting. When both shells are turned on, electron‐phonon scattering is noticed to be the dominant phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…[75,143,144] It has been shown that the inner shell can be electrically active where both shells contribute similarly to the transport. [145][146][147] For this reason, DWCNTs are better intrinsic conductors than large MWCNTs (in which not all shells are coupled) and possibly better than SWCNTs, [148][149][150] while maintaining a high degree of chemical stability. [74] Further, functionalization can happen exclusively on the outer shell, leaving the inner tube intact and isolated.…”
Section: Multi-wall Cntsmentioning
confidence: 99%
“…Provided a large enough interwall resistivity, , the outer wall(s) would act as sheathing, while current would flow through the inner wall. Moreover, other FWCNT coils that have a semiconducting outer wall(s) and a metallic inner wall(s) could possibly avoid short-circuiting, particularly when tested at low temperatures. ,, Positively gating the p -type semiconducting outer wall(s), thereby depleting it from charge carriers, could further turn it into sheathing. Previous works suggested that near the source and drain electrodes, gating is less effective, allowing current to pass from the electrodes, through the outer wall, to the inner wall. ,, Generally, ∼22% of DWCNTs are expected to have the M@S (i.e., metallic inside semiconducting) electronic configuration and ∼15% of TWCNTs are expected to have the M@S@S configuration .…”
mentioning
confidence: 99%